THE POLITENESS STRATEGIES USED BY THE BARISTAS OF‘’STARBUCKS COFFEE’’ IN COMMUNICATING WITH THE CUSTOMERS - Novinsky P Samianto; Esther H Kuntjara (Institute of Research and Community Outreach - Petra Christian University, 2016)
This is a study about Politeness Strategies used by the Baristas of Starbucks Coffee in communicating with their customers. The writer is interested in analyzing the politeness strategies used by the baristas in welcoming, offering and inquiring their customers. In my study, the writer uses the theory of politeness proposed by Scollon and Scollon (2001). The writer uses the method of descriptive approach supported by quantitative data. The writer found that in welcoming their customers all the baristas tend to use positive politeness strategy which is notice or attend hearer and the negative politeness is use family names or titles. The writer found the most politeness strategies used by the baristas in inquiring the customers are Positive politeness strategy of claim common point of view, opinion, attitudes, knowledge, empathy and the negative politeness used is Give H the option not to do the act. Lastly, in inquiring, all the baristas tend to use negative politeness strategy of making minimal assumption and the positive politeness strategy the most used is indicate S knowH’s.